2009
DOI: 10.1161/atvbaha.109.186502
|View full text |Cite
|
Sign up to set email alerts
|

SR-BI Selective Lipid Uptake

Abstract: Objective-The purpose of this study was to investigate the interaction of SAA and SR-BI in remodeling of acute phase HDL (AP HDL). Methods and Results-We used SAA and SR-BI adenoviral vector expression models to study the interaction between these entities. SR-BI processing of mouse AP HDL generated progressively smaller discreet HDL particles with distinct apolipoprotein compositions. SR-BI actions segregated apolipoproteins with the smallest particles containing only apoA-I. Larger remnants contained apoA-I,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 26 publications
0
3
1
Order By: Relevance
“…4A ). These fi ndings contrast to what we have previously shown to occur with HDL core remodeling by SR-BI ( 19 ) and repeat here for illustrative purposes ( Fig. 4B ).…”
Section: Effect Of Saa On El-mediated Hdl Remodeling In Vivocontrasting
confidence: 78%
See 2 more Smart Citations
“…4A ). These fi ndings contrast to what we have previously shown to occur with HDL core remodeling by SR-BI ( 19 ) and repeat here for illustrative purposes ( Fig. 4B ).…”
Section: Effect Of Saa On El-mediated Hdl Remodeling In Vivocontrasting
confidence: 78%
“…Whether the presence of SAA on HDL can modulate HDL remodeling by EL has not been investigated. Previous studies from our laboratory showed that in the presence of SAA, perturbation of HDL core and surface lipid by scavenger receptor class B type I (SR-BI) leads to generation of small, lipid-depleted apoA-I that is susceptible to catabolism ( 19 ). In this study, we carried out in vitro and in vivo studies to investigate whether the presence of SAA infl uences EL-mediated metabolism of HDL.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…It was also confirmed by that serum SAA levels were correlated with relative lag times in all samples ( Figure 8 D). In general, HDL-Cho levels in patients with severe inflammation are lower than that in normal subjects, because of accelerated catabolism of SAA-HDL [ 1 , 29 ]. HDL-Cho concentrations within the High SAA group were 22% lower compared with those observed within Low SAA group ( Figure 8 C).…”
Section: Discussionmentioning
confidence: 99%